Transcription Factors Sox2 and Sox3 Directly Regulate the Expression of Genes Involved in the Onset of Oligodendrocyte Differentiation - Rupprecht, Jesse; Reiprich, Simone; Baroti, Tina; Christoph, Carmen; Sock, Elisabeth; Fröb, Franziska; Wegner, Michael (Cells, 2024)
Rapid information processing in the central nervous system requires the myelination of axons by oligodendrocytes. The transcription factor Sox2 and its close relative Sox3 redundantly regulate the development of myelin-forming oligodendrocytes, but little is known about the underlying molecular mechanisms. Here, we characterized the expression profile of cultured oligodendroglial cells during early differentiation and identified Bcas1, Enpp6, Zfp488 and Nkx2.2 as major downregulated genes upon Sox2 and Sox3 deletion. An analysis of mice with oligodendrocyte-specific deletion of Sox2 and Sox3 validated all four genes as downstream targets in vivo. Additional functional assays identified regulatory regions in the vicinity of each gene that are responsive to and bind both Sox proteins. Bcas1, Enpp6, Zfp488 and Nkx2.2 therefore likely represent direct target genes and major effectors of Sox2 and Sox3. Considering the preferential expression and role of these genes in premyelinating oligodendrocytes, our findings suggest that Sox2 and Sox3 impact oligodendroglial development at the premyelinating stage with Bcas1, Enpp6, Zfp488 and Nkx2.2 as their major effectors.
CRIS-Team Scopus Importer:2024-06-21
Keywords: glia; myelin; Nkx2.2; SoxB1 proteins; transcription factor; Zfp488